Enhanced NIR-I emission from water-dispersible NIR-II dye-sensitized core/active shell upconverting nanoparticles - Hazra, Chanchal [UNESP]; Ullah, Sajjad [UNESP]; Serge Correales, York E. [UNESP]; Caetano, Laís G. [UNESP]; Ribeiro, Sidney J. L. [UNESP] (Royal Society of Chemistry (RSC), 2018)
Recently, there has been a surge in research studies directed towards near-infrared (NIR) dye-sensitized upconverting nanoparticles (UCNPs) as they carry the prominent advantages of a broader absorption range and enhanced upconversion efficiency. Unfortunately, however, the UCNPs combined with the native form of NIR dye are of little use for biological imaging in the NIR-I or NIR-II window as the dye- sensitization process is mostly carried out in non-aqueous media. To overcome this shortcoming, we propose to employ a water-dispersible NIR-II dye (IR-1061) to sensitize core/active shell UCNPs and achieve sufficiently high upconversion quantum efficiency in aqueous media. We have particularly focused on achieving strong NIR-I emission rather than visible upconversion emission as the latter suffers from the problem of shallow tissue penetration depth. For this purpose, Pluronic F68-encapsulated water-dispersible IR-1061 dye was coupled with polyethyleneimine (PEI)-coated NaYF4:Tm3+/Yb3+@NaYF4:Yb3+ core/active shell UCNPs. We thus achieved a 283% enhancement in NIR-I emission (i.e. 800 nm emission of Tm3+ ion) from water-dispersible NIR-II dye-sensitized core/active shell UCNPs via doping of ytterbium ions (Yb3+) in the UCNP shell, which bridged the energy transfer from the dye to the UCNP core. Practically, in comparison with the native form of the dye, this water-dispersible dye can also efficiently harvest irradiation energy, which is nonradiatively transferred to Yb3+ ions in the shell and subsequently to Yb3+ ions in the core. The latter sensitizes Tm3+ ions positioned in the core, thus generating upconversion luminescence from the UCNPs. We envision that our water-dispersible NIR-II dye-sensitized core/active shell UCNPs are not only potential candidates for a broad spectrum of photonic applications but that they will also find new opportunities in several biological applications.